Pengaruh Social Media Marketing, Brand Ambassador dan Electronic Word of Mouth Terhadap Keputusan Pembelian pada Produk Jiniso - Ikrimah Rahmaniyah; Elok Vilantika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Purchase decisions play an important role in the success of marketing and selling a brand's products, one of which is the Jiniso fashion brand. The study aims to analyze the influence of social media marketing, brand ambassadors, and electronic word of mouth on purchasing decisions. The research method used is quantitative with the Partial Least Squares-Structural Equation Modeling approach. The sample of this study was one hundred and sixty respondents with a purposive sampling technique. The results of the study show that each variable has a significant influence on purchasing decisions. This study concludes that an active and consistent presence on social media platforms such as Instagram, TikTok, and e-commerce such as Shopee allows brands to build engagement with their followers. Through uploading relevant content supported by positive product reviews by consumers, seasonal promotional campaigns demonstrated by brand ambassadors are able to create a strong foundation for a brand's image and encourage purchasing decisions for Jiniso fashion products. These findings are expected to be a consideration for companies in designing more appropriate and efficient marketing strategies in the digital era in order to improve purchasing decisions and company competitiveness.